Sleep and sleep deprivation differentially alter white matter microstructure: A mixed model design utilising advanced diffusion modelling - Irene Voldsbekk; Inge Groote; Nathalia Zak; Daniël Roelfs; Oliver Geier; Paulina Due-Tønnessen; Lise-Linn Løkken; Marie Strømstad; Taran Y. Blakstvedt; Yvonne S. Kuiper; Torbjørn Elvsåshagen; Lars T. Westlye; et al. (NeuroImage, 2021)
Sleep deprivation influences several critical functions, yet how it affects human brain white matter (WM) is not well understood. The aim of the present work was to investigate the effect of 32 hours of sleep deprivation on WM microstructure compared to changes observed in a normal sleep-wake cycle (SWC). To this end, we utilised diffusion weighted imaging (DWI) including the diffusion tensor model, diffusion kurtosis imaging and the spherical mean technique, a novel biophysical diffusion model. 46 healthy adults (23 sleep deprived vs 23 with normal SWC) underwent DWI across four time points (morning, evening, next day morning and next day afternoon, after a total of 32 hours). Linear mixed models revealed significant group × time interaction effects, indicating that sleep deprivation and normal SWC differentially affect WM microstructure. Voxel-wise comparisons showed that these effects spanned large, bilateral WM regions. These findings provide important insight into how sleep deprivation affects the human brain.